2020
DOI: 10.1016/j.jpeds.2019.12.054
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Regulation of HSD11B1 and HSD11B2 Predicts Glucocorticoid Sensitivity in Childhood Acute Lymphoblastic Leukemia

Abstract: There are few biomarkers to predict efficacy of glucocorticoid treatment in childhood acute lymphoblastic leukemia (ALL) at diagnosis. Here, we demonstrate reciprocal regulation of 11β-HSD, may predict the apoptotic response of ALL to glucocorticoid treatment. Our data may be useful to refine glucocorticoid treatment, to retain benefit whilst minimizing sideeffects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…As for Hydroxysteroid 11-Beta Dehydrogenase 1 HSD11B1, its translation product is a catalyst for the generation of corticosteroids. Current research believes that its function is mainly concentrated in endocrine (22,23).…”
Section: The Correlation Of Aqp9 Expression With Survival and Clinical Characteristicsmentioning
confidence: 99%
“…As for Hydroxysteroid 11-Beta Dehydrogenase 1 HSD11B1, its translation product is a catalyst for the generation of corticosteroids. Current research believes that its function is mainly concentrated in endocrine (22,23).…”
Section: The Correlation Of Aqp9 Expression With Survival and Clinical Characteristicsmentioning
confidence: 99%
“…82 In a subsequent study of children ALL, decreased 11β-HSD1 expression and/or increased 11β-HSD-2 expression were associated with GC resistance. 83 These studies indicate that 11β-HSD-1/2 play an important role in GCR occurrence.…”
Section: Impaired Nuclear Translocation Of the Gr Complexmentioning
confidence: 79%
“…Compared with GC‐sensitive NS patients, 11β‐HSD‐2 mRNA was increased in peripheral blood mononuclear cells of GC‐resistant patients 82 . In a subsequent study of children ALL, decreased 11β‐HSD1 expression and/or increased 11β‐HSD‐2 expression were associated with GC resistance 83 . These studies indicate that 11β‐HSD‐1/2 play an important role in GCR occurrence.…”
Section: Glucocorticoid Resistancementioning
confidence: 81%
“…19 In human T-lymphoblastic leukaemia cells, both HSD11B2 expression and reciprocal regulation of HSD11B1 and HSD11B2 have been shown to be associated with glucocorticoid resistance. 20,21 Data for tissue resistance to glucocorticoid activity are limited in critical illness. Indirect evidence suggesting altered tissue HSD11B activity comes from studies that found increased plasma cortisol:cortisone ratio in critically ill septic and trauma patients.…”
Section: Discussionmentioning
confidence: 99%